TOTAL PHENOLIC AND FLAVONOID CONTENTS AND ANTIOXIDANT ACTIVITY OF ETHANOL FRACTION OF PICRIA FEL-TERRAE (LOUR.) HERBS - Sitorus, Panal; Hasibuan, Poppy Anjelisazaitun; Satria, Denny (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To evaluate total phenolic, flavonoid content (TFC and TPC) andantioxidant activity of ethyl acetate fraction (ETF) of Picria fel-terrae Lour. herbs. Methods: TPC and TFC in ETF were determined by Folin–Ciocalteu and colorimetric methods, and antioxidant activity was determined by 1,1-diphenyl- 2-picrylhydrazyl (DPPH) method. Results: ETF was found to contain low levels of phenolic (17.71±1.26 mg gallic acid equivalent/g), total flavonoid (14.43±0.03 mg quercetin equivalents/g). Antioxidant activity from DPPH assay was measured as inhibitory concentration 25.72±0.13 μg/mL. Conclusions: The results reveal that ETF of P. fel-terrae Lour. herbs has strong antioxidant activity. Our further study is to the isolation of compounds which responsible for antioxidant components.